Ribonucleic Acid Polymerase Catalyzing Synthesis of Double-stranded Arbovirus Ribonucleic Acid - Martin, E. M. (1967)
The large-particle fraction from the cytoplasm of chick embryo fibroblasts infected with Semliki Forest virus was found to catalyze the incorporation of the 5′-triphosphates of guanosine, adenine, cytidine, and uridine into an acid-insoluble alkali-labile product. The conditions affecting the preparation and assay of this enzyme were investigated. The ribonucleic acid (RNA) polymerase was not present in uninfected cells, and it appeared in infected cells at the time of rapid viral RNA synthesis. The polymerase was found to catalyze the synthesis of a species of RNA which was resistant to ribonuclease and which exhibited the sedimentation properties, buoyant density, and thermal transition temperature of the double-stranded RNA found in vivo in chick cells infected with Semliki forest virus. Attempts to demonstrate that the reaction product of this enzyme also included single-stranded viral RNA were not successful. Although other interpretations are possible, these results give some support to the suggestion that more than one enzyme may be involved in the replication of viral RNA.